The Mahathir effect in Malaysia's 2018 election: the role of credible personalities in regime transitions. Issue 3 (3rd April 2019) - Abdullah, Walid Jumblatt
ABSTRACT: The 14th Malaysian General Elections (Pilihanraya Umum, 14, PRU 14) in 2018 proved to be a watershed election as Barisan Nasional (National Front, BN) lost power for the first time in history. Pakatan Harapan (Alliance of Hope, PH), led by former BN leader and Prime Minister Mahathir Mohamad, captured the majority of parliamentary seats. This article analyses the impact of Mahathir specifically, and credible personalities in general, in unseating dominant one-party regimes. I argue that credible personalities are vital in causing transitions in dominant one-party systems. Explanations on transitions from authoritarian regimes in the literature have typically revolved around incumbent weakness and opposition strength. While dissatisfaction toward the regime is a necessary condition for transition, it is not sufficient. Personalities which can adequately appeal to the masses are important to bridge the credibility gap which the opposition may otherwise have to grapple with. Mahathir's presence in the opposition was crucial to PH's victory, as he provided the credibility boost which the opposition needed. This was particularly important for Malay voters. This study is situated within the literature on parties, elections and democratization.